Amino acid-derived imidazole zwitterion as green interfacial corrosion inhibitor for cold rolled steel - Wan Mohd Norsani Wan Nik; Jiyaul Haque; Mohd Sabri Mohd Ghazali; Atria Pradityana; Izionworu Vincent Onuegbu; Walid Daoudi; Elyor Berdimurodov; Ahmed Abdulamier Al-Amiery (Case Studies in Chemical and Environmental Engineering)
A natural amino acid methionine-derived imidazole zwitterion was synthesized and investigated as a corrosion inhibitor on cold-rolled steel in an acid environment using weight loss, electrochemistry, and SEM techniques. The synthesized imidazole zwitterion inhibitor was fulfilled with green parameters: multicomponent single-step reaction, reaction at ambient temperature, and water used as a solvent. The corrosion study results show that imidazole zwitterion exhibits effective inhibition efficiency (84 %) at very low concentrations (100 ppm). The imidazole zwitterion exhibited excellent inhibition efficiency (72 %) at high temperature (95 °C). SEM results supported the experimental findings. The adsorption of imidazole zwitterion obeys the Langmuir adsorption isotherm with a uniform inhibitor film achieved via physical and chemical adsorption mechanisms. Imidazole zwitterion can be useful in low inhibitor concentration applications such as pipeline flushing and cleaning.